Hubungan Pengetahuan Ibu dengan Upaya Deteksi Dini Kanker Payudara Melalui Sadari di Kelurahan Nglames kabupaten Madiun - Rika Maya Sari (STIKes Patria Husada Blitar, 2015)
In Indonesia, based on data from the Global Burden of Cancer (Globocan), breast cancer in women (26 per 100,000), followed by uterus cancer (16 per 100,000). The easiest way and does not require a fee for early detection of breast cancer is the breast self examination (BSE). The purpose of study was to analyze the correlation of women knowledge and early detection of breast cancer through the BSE. The design was analytic cross sectional study with the sample of 98 mothers in the village Nglames Madiun district. The data was collected using questionnaires and analyzed with Chi Square. The results showed most women had the knowledge and efforts of BSE well and there was a correlations between women’s knowledge and early detection of breast cancer through the BSE with a significance level of p value 0,010 <0,05. The women were expected to enhance the knowledge about early detection of breast cancer and for health centers to improve health education efforts in the community about the importance of early detection of breast cancer.